Science and technology in modern China, 1880s - 1940s - Tsu, Jing; Elman, Benjamin A. (China studies, 2014)
The first of its kind, this collection of critical essays opens up new venues in the comparative study of science and culture by focusing on the formative decades of modern China in the late nineteenth and first half of the twentieth century. It provides a wide-ranging examination of the cultural and intellectual history of science and technology in modern China.From anti-imperialism to the technology of Chinese writing, the commodification of novelties to the rise of the modern professional scientist, new lexica and appropriations of the past, the contributors map out a transregional and global circuitry of modern knowledge and practical know-how, nationalism and the amalgamation of new social practices
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Geschichte 1880-1950; Technik; Naturwissenschaften; China